A novel approach for multivariate process monitoring using several intelligences, ISSN / e-ISSN ‎1748-5045 / 1748-5045 - Rezki Nafissa; Kazar Okba; Mouss Leila Hayet; Kahloul Laid (International Journal of Industrial and Systems Engineering, 2017)
This paper presents a multi-agent system for multivariate process monitoring. The proposed multi-agent system combines several intelligences which are: multivariate control charts, neural networks, Bayesian networks, and expert systems. This system aims to realise a complete control of complex industrial process. In order to demonstrate the efficiency of the proposed multi-agent system, it has been applied and evaluated in the monitoring of the complex process Tennessee Eastman process (TEP).